2010
DOI: 10.1007/s00167-010-1242-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for ACL deficiency in patients over 50

Abstract: When faced with ACL deficiency, physiological age, condition of the knee at the time of examination, life expectancy and activity level are probably more important than chronologic age. In the present study, arthroscopic surgery for the management of ACL tear and secondary lesions provides comparable clinical outcomes in middle-aged patients and in patients aged below 30.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(112 citation statements)
references
References 31 publications
10
93
1
Order By: Relevance
“…Operative treatment documented favorable outcomes in this patient population with regard to knee stability and patient satisfaction, with results similar to those observed in a younger patient population [15, 19, 21, 23]. Among the four studies reporting on the difference in the outcomes between elderly and young patients, no increased risk of complication (stiffness, arthrofibrosis, infections) was noted in the middle-aged patients compared to the control group [15, 19, 21, 23].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Operative treatment documented favorable outcomes in this patient population with regard to knee stability and patient satisfaction, with results similar to those observed in a younger patient population [15, 19, 21, 23]. Among the four studies reporting on the difference in the outcomes between elderly and young patients, no increased risk of complication (stiffness, arthrofibrosis, infections) was noted in the middle-aged patients compared to the control group [15, 19, 21, 23].…”
Section: Discussionsupporting
confidence: 74%
“…Mostly level III studies were reported, either case–control [15, 2023] or retrospective cohort [13, 2428] studies. Five were case series (level IV) [14, 2932].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 19 studies, 2 studies 5,33 were rated as level of evidence II, 6 studies 6,9,33,39,51,63 qualified as level III, and 11 studies g were classified as level IV. Table 4 illustrates the mean AMS for each study and corresponding level of evidence rating provided by the 4 independent reviewers.…”
Section: Ams and Level Of Evidencementioning
confidence: 99%
“…Historically, conservative measures have provided good results in most patient [1][2][3] , however the increasing understanding of the natural history of PCL insufficiency has induced many surgeons to recommend reconstruction or augmentation to prevent decline of the knee function in the short term, and the development of osteoarthritis of the patello-femoral joint and the medial compartment in the long term 4 , secondary to the damage to cartilage and meniscal tears [5][6][7][8][9] . Surgical reconstruction is usually recommended in symptomatic patients with grade III PCL tears who complain of pain and instability, and in those with multiple ligament injuries.…”
Section: Introductionmentioning
confidence: 99%